Self-Disclosure at Pre-Marriage Stage and its Relationship to Marital Adjustment among Health Sector Employees in Irbid Governorate - Feras Qurit'e Hussien Al-jobour; Shima'a Mo'ath Ahmed Lababneh (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: This study aims to investigate the relationship between self-disclosure in pre-marriage stage and its relationship to marital adjustment among health sector employees in Irbid Governorate, Jordan. Methods: The study relied on a correlational descriptive approach. The study sample consisted of (400) participants (200 husbands, 200 wives); who were selected using a convenient sampling method. To achieve the objectives of the study, two scales were developed: the first scale was to measure self-disclosure in the per-marriage stage and the second scale was to measure marital adjustment. Validity and stability of both scales were verified. Results: The results of the study reveal that the level of self-disclosure among participants in per-marriage stage was medium, while the level of marital adjustment was high. There was a significant positive correlation between self-disclosure in per-marriage stage and marital adjustment among participants. The results also showed that there were statistically significant differences in the level of self-disclosure in the per-marriage stage due to the choice method, in favor of the individual choice, and due to the age difference between husbands and wives, in favor of eight years and above. Conclusions: The study recommends raising awareness about the importance of self-disclosure between partners to be married. It also recommends encouraging marriage counseling centers to hold courses for those who are about to get married to train them on self-disclosure skills.